The research of nonuniform temperature field in the functional capacity of the microwave- drier - Потапов, Владимир Алексеевич; Цуркан, Николай Михайлович; Андрюшин, Илья Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The problem of relative unevenness determination of the temperature field into the functional capacity of investigated microwave - drier is considered